About the word usage of the writer Kemel Tokayev (based on the novel “The Soldier Went to War”) - Gabdrakhman, Т.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article examines the language and style of literary works of the detective genre. The object of the study is the work of Kemel Tokayev, who wrote the first works in this genre in Kazakh literature, including the novel “The Soldier Went to War”. The works of the writer, which is comprised of detective prose works, occupies a significant position within the corpus of Kazakh literature. The purpose of the article is to determine the linguistic and stylistic features of the Kazakh detective genre. In this regard, the tasks of analyzing the use of synonyms, antonyms, comparisons, metaphors and epithets were set. In the novel A Soldier Went to War, a wide use of the potential of synonymy is noticed: both systematic and contextual synonyms are freely used. These synonyms form gradational development in the text. When synonyms are used in the same row, the fact that one of them has an emotionally expressive coloring can be explained by the peculiarity of the writer’s language. Pleonastic usages also serve to clarify the idea. In the novel, there is naturally less use of antonyms than of synonyms, since they are needed only to compare phenomena in a certain passage of text. The use of such tropes as comparison, metaphor, epithet in the text is described, their artistic function and methods of formation are determined. Linguistic facts were presented in context, as their meaning and meaning are often revealed through context. An analysis was carried out to determine the role of synonyms, antonyms, epithets and metaphors in the text of detective novels in creating a tense atmosphere, plot development and characterization of characters. The study is based on methods of stylistic analysis and focuses on specific linguistic techniques used by the author to achieve the effect of intrigue and mystery characteristic of the detective genre. The results of the study allow us to better understand the peculiarities of the linguistic nature of detective works and their impact on reader perception.